2010
DOI: 10.1007/s00280-010-1259-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-alkalinization without hyper-hydration for the prevention of high-dose methotrexate acute nephrotoxicity in patients with osteosarcoma

Abstract: (204 words)Purpose: To evaluate the reliability and renal safety of an original schedule of high-dose methotrexate (HDMTX) administration with hyper-alkalinization, and without hyperhydration.Methods: Osteosarcoma patients received HDMTX (8-12 g/m²) as a 4-hour infusion.Hypertonic 8.4% sodium bicarbonate was infused prior to HDMTX, then once daily for 3 days. Methotrexate serum concentrations was measured at hour 4 (Cmax), hour 24, hour 48 and hour 72. Urinary pH was measured on each miction. Serum creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
(35 reference statements)
6
17
0
1
Order By: Relevance
“…Human studies have reported beneficial effects of sodium bicarbonate in reducing blood acidosis and kidney toxicity in chemotherapy patients [7,21]. Therefore, we developed a new preclinical method to minimize damage to renal functions (assessed by measurements of creatinine levels, kidney weight ratio and urine pH) and improve general health (weight gain, normal body temperature and reduced mortality) in rodent subjects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Human studies have reported beneficial effects of sodium bicarbonate in reducing blood acidosis and kidney toxicity in chemotherapy patients [7,21]. Therefore, we developed a new preclinical method to minimize damage to renal functions (assessed by measurements of creatinine levels, kidney weight ratio and urine pH) and improve general health (weight gain, normal body temperature and reduced mortality) in rodent subjects.…”
mentioning
confidence: 99%
“…Cisplatin is partially metabolized into toxic species [30], promoting an acidic environment that produces nephrotoxicity and changes in renal functions, documented by increases in creatinine (normal creatinine between 0.2 –1.36 mg/dL) and kidney weight ratio [13,15] in our study. A change in the body pH (normal blood pH: 7.35–7.45; normal urine pH ~7.00) toward acidity (below pH 7.0) favours oxygen to be driven out of the body, thereby facilitating cancer cell survival [10,12,21]. Thus, urine, but not blood, pH would be expected to be increased by alkaline and decreased by acidic diets/treatments, as observed in our study and elsewhere [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of malignancy in osteosarcoma are high, patient prognosis is poor, and patients may exhibit lung metastases within several months. Subsequent to amputation, the 3-5-year survival rates are only 60% (19). The present study observed that salvianolic acid B suppressed cell proliferation, induced apoptosis and activated cleaved caspase 3 of the osteosarcoma MG63 cell.…”
Section: Discussionmentioning
confidence: 80%
“…Antifolates have been used in cancer treatment since 1948 when aminopterin was first shown to cause temporary remission of disease in children with acute lymphoblastic leukemia (ALL) (Farber and Diamond, 1948). Today, the most widely used antifolate, methotrexate (MTX), is used in the treatment of multiple diseases including ALL, osteosarcomas, lymphomas, head and neck, bladder, and breast cancer (Catto and Hamdy, 2010; Mikkelsen et al, 2011; Mir et al, 2010; Tobias et al, 2010). …”
Section: Methotrexatementioning
confidence: 99%